Genome-wide DNA methylation analysis of Astragalus on the intervention of ID2 promoter via PI3K/Akt signaling pathway in peritoneal fibrosis - Manshu Yu; Junyi Zhao; Yun Shan; Huibo Dai; Lei Tang; Li Sheng; Lu Zhang; Meixiao Sheng (Scientific Reports)
Abstract Peritoneal dialysis (PD) is a successful renal replacement therapy for end-stage renal disease. Continuous infiltration of bioincompatible PD fluid causes mesothelial-mesenchymal transition (MMT) of peritoneal mesothelial cells (PMCs), leading to peritoneal fibrosis (PF). DNA methylation has been characterized as an important regulatory mechanism on multiple fibrosis. However, the mechanisms by which DNA methylation regulates PF are not fully understood resulting in a lack of disease-modifying drugs. Astragalus membranaceus (Astragalus) is naturally phytomedicine that has immunoregulation properties. The study aimed to elucidate the underlying mechanisms of Astragalus in regulating DNA methylation and anti-PF capabilities. In vivo PD rat models were established by inducing with high-glucose PD fluid and Astragalus was intraperitoneal injection. Global DNA methylation sequencing was used to compare the DNA methylation status between control and PF rat models. Methylation profiles and KEGG analysis were identified a possible methylated target gene and its correlation pathway. Through real-time PCR and western blotting, candidate markers and pathways were validated in vivo and in vitro. Chromatin immunoprecipitation and luciferase assays were used to identify the prediction of DNA methyltransferase (Dnmts) binding with methylated target gene. The functions of the validated pathways were further investigated using the knockdown or overexpression strategy. In vivo and in vitro, Astragalus treatment showed a protective effect against PF and Dnmts, characterized by improving pathological manifestation, ameliorating MMT markers, and reducing Dnmt1/3a proteins. Inhibitor of DNA-binding 2 (ID2) was investigated in target gene by integrating the mRNA and methylation profiles involved in PF and Astragalus treatment. PF induced the methylation of ID2 that resulted in recruitment of the Dnmt3a and decreased ID2 expression. The increased ID2 expression in response to Astragalus is a consequence of demethylation in promoter. In addition, phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway correlated with PF, knockdown or overexpression of ID2 regulated this pathway and MMT of PMCs. Astragalus ameliorated PF by targeting Dnmt3a mediated ID2 promoter via PI3K/Akt signaling pathway. The epigenetic regulation of DNA methylation existed the critical role in attenuating PF.